MENGENAL DIGITAL MARKETING DALAM PENGEMBANGAN EKONOMI KREATIF - Rini Widianingsih; Icuk Rangga Bawono; Agus Sunarmo; Irianing Suparlinah (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Today's digital era, the use of information and communication technology has a major and important role in increasing the competitiveness of a country. The development of Society 5.0 or Industrial Revolution 5.0 which was previously the Industrial Revolution 4.0 had an unavoidable impact. One sector that is recognized as having great potential in supporting national economic growth in Indonesia is the creative economy sector. One of the problems faced by creative economy entrepreneurs is the problem of marketing to increase income. One of the solutions that can be done to improve product marketing from the results of the creative economy in society is to use the Digital Marketing model. the use of digital media is expected to be able to reach a wider target market. In terms of content or content, digital marketing is not much different from conventional marketing.Digital marketing training is carried out by following the steps provided in the Digital marketing instructions and strategies provided by the service team.